ADULT GRANULOSA CELL TUMORS: A COMPREHENSIVE REVIEW OF CLINICOPATHOLOGICAL FEATURES AND MOLECULAR INSIGHTS - Liana, Nana; Helmizar, Roland; Ruhsyahadati, Ruhsyahadati; Triyana, Rahma; Rasyid, Lismawati; Aliefia, Desi (Nusantara Hasana Journal, 2024)
Adult granulosa cell tumor (AGCT) is a rare subtype of ovarian cancer, accounting for 2-5% of all ovarian malignancies and originating from granulosa cells that are involved in oocyte development and sex steroid production. Although AGCT is often diagnosed at an early stage and has a better prognosis compared to other types of ovarian cancer, challenges in diagnosis persist. Clinical symptoms such as abdominal pain and distension are often nonspecific and may be accompanied by signs of hyperestrogenism. Histopathological examination of AGCT reveals a characteristic cell pattern; however, variations in histological appearance can complicate diagnosis. Despite a favorable prognosis, there remains a risk of recurrence, with many cases experiencing relapse several years post-initial treatment. This underscores the necessity for long-term monitoring of patients following treatment. This article aims to explore the clinicopathological characteristics of AGCT and provide guidance for more effective patient management through a deeper understanding of molecular mechanisms and appropriate therapeutic approaches